Barriers Influencing Vaccine Development Timelines, Identification, Causal Analysis, and Prioritization of Key Barriers by KOLs in General and Covid-19 Vaccine R&D - Janse, Marga; Brouwers, Thomas; Claassen, Eric; Hermans, Peter; van de Burgwal, Linda (Frontiers in Public Health, 2021)
One of the key factors in the development of vaccines are the development timelines in the vaccine development process. There are indicators that these timelines are nowadays prohibitively long and currently is between 15-20 years. A direct consequence of the increase in vaccine development timelines is the delay in their societal benefit. Additionally, increasing development timelines threaten the ability to respond quickly to emerging pathogens. These are increasing at surprising all-time high rates of over one per year and spreading quicker than ever. Using the barrier approach, this present study identified key barriers causes for delay, as experienced by key-opinion-leaders (KOLs) in the vaccine development process. These innovation barriers are visualized, and their underlying causes revealed by means of qualitative root cause analysis. Furthermore, a quantitative ranking of the barriers was used to demonstrate their relative importance for both regular vaccine development as for Covid-19 vaccine development. This study shows a clear difference in KOL perception of barriers hampering timelines in general vaccine development being; ‘Limited ROI for vaccines addressing disease with limited market size’, ‘Limited ROI for vaccines compared to non-vaccine projects’, ‘Academia not being able to progress beyond proof of principal’ in contrast to a markedly different set of barriers being specific for Covid-19 vaccine development; ‘Lack of knowledge concerning pathogen target’, ‘High risk of upscaling unlicensed vaccines’ and ‘Proof of principal not meeting late-stage requirements’. Visualizing impact by means of the VIC model shows that all identified barriers are of influence on almost all stages of the VIC. Demonstrating that the phase between late development and the end of phase III is being impacted the most. Clearly the most impactful barriers were linked to funding and ROI, the hand-off point between academia and industry, and a lack of knowledge of pathogen targets. These new findings should be put in perspective of both access & benefit sharing under the Nagoya protocol and technological solutions relating to ownership and inventorship under Covid-19.